Effect of in-plane fiber waviness on the failure of fiber reinforced polymer composites - Narayanan, Swaroop (2018)
As the demand for energy increases day by day, the future relies more on clean renewable energy resources. Wind turbines have a promising active contribution to meet this future demand. Wind industries are more interested to have bigger turbines to produce more power economically from a single turbine unit. Glass and carbon fiber composite materials are largely used in the light weight turbine blade manufacturing due to their high strength to weight ratio. The spar-cap is considered as the back bone of a wind turbine blade and it consists of significant amount of unidirectional laminates. Manufacturing defects are unavoidable due to their nature and involvement in the structure. Some of these defects may affect the life expectancy of the blade as well as the whole turbine unit. Focus of the present study is related to a common manufacturing defect found in spar cap regions, ‘fiber waviness’, and its influence towards the failure initiation and propagation under compression and bending loads. Despite its wide spread occurrence, in-plane fiber waviness defect found throughout the thickness of composite laminates is not well studied. Therefore, a coupon level in-plane fiber waviness defect was induced in unidirectional composite samples and tested under numerous loading conditions. Variations in both mechanical strength and failure modes of waviness induced samples were characterized. In addition, double cantilever beam experiments were conducted to study the effect of fiber waviness on the fracture energy and crack propagation. Further, an analytical model has been prepared by adding sinusoidal waviness into the laminate to estimate the reduction in modulus based on the constitutive relations. Also, finite element analysis was used to predict the compressive strength and failure modes under the static compression loads based on a physical based failure theory (LaRC02) using ABAQUS 6.13TM software. Finally, a 6-m wind turbine blade shell model was designed using NuMAD software. Fiber waviness was introduced at various locations of the spar-cap region and a static flap-wise bending analysis was performed at designed maximum bending moment of the blade. The longitudinal strain deformation during flap-wise bending analysis at the fiber waviness region of those blade models was validated with the help of four-point bending test of a composite I - beam consisting of waviness defect.